2017
DOI: 10.1109/tcbb.2016.2515594
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Circular Permutations by Super Short Reversals

Abstract: We consider the problem of sorting a circular permutation by super short reversals (i.e. reversals of length at most 2), a problem that finds application in comparative genomics. Polynomial-time solutions to the unsigned version of this problem are known, but the signed version remained open. In this paper, we present the first polynomial-time solution to the signed version of this problem. Moreover, we perform experiments for inferring phylogenies of two different groups of bacterial species and compare our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In 2016, Galvão et al [ 14 ] proved that Sorting Signed Permutations by cyclic super short reversals is also in . Given a signed permutation and a VD-vector X , let be the set of elements from such that is even and , and let be the set of elements from such that is odd and .…”
Section: Related Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Galvão et al [ 14 ] proved that Sorting Signed Permutations by cyclic super short reversals is also in . Given a signed permutation and a VD-vector X , let be the set of elements from such that is even and , and let be the set of elements from such that is odd and .…”
Section: Related Resultsmentioning
confidence: 99%
“…The following property was given by Jerrum [ 13 ]. Note that the author mistakenly wrote , which was later corrected by Galvão et al [ 14 ].…”
Section: Preliminaries and Notationsmentioning
confidence: 99%
“…Aside from problems that consider rearrangement length, little is known about weighted rearrangements [ 16 20 ]. In [ 9 ], we showed that with a simple cost function based on a partition of the adjacencies of one of the genomes into equivalence classes, one can choose—from the exponentially large set of shortest scenarios—a scenario that minimizes the number of moves acting across classes.…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…Recently, the full version of the conference paper corresponding to Chapter 6 has been accepted for publication in IEEE/ACM Transactions on Computational Biology and Bioinformatics [Galvão et al 2016]. The first relevant difference between the journal version and the conference version of the paper is that the journal version contains expanded explanations and expositions of the methods.…”
Section: Contributions and Organizationmentioning
confidence: 99%